2011
DOI: 10.1007/s11258-011-9947-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional groups and dispersal strategies as guides for predicting vegetation dynamics on reclaimed mines

Abstract: The development of species richness and plant cover through time are two important measures that are often used to assess success in land reclamation schemes. We expand this approach by considering functional groups in terms of life-history traits and dispersal strategies, as important components of ecosystem function and colonisation. Here, we test, if the species richness and cover of these functional groups are changed during post-treatment succession in 26 reclaimed coal mines, and whether these changes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
2
25
2
10
Order By: Relevance
“…Soil moisture, nutrients and microbial assemblages are critical determinants of seed germination and plant growth and development; whereas, soil texture is important for the development of plant roots (Jung, Duan, House, & Chang, ) and for the retention of water and nutrients in the soil (Hillel, ; Leatherdale, Chanasyk, & Quideau, ). Furthermore, forest floor material typically contains a large seed bank that can be beneficial for establishing a plant community during restoration/reclamation (Alday, Pallavicini, Marrs, & Martínez‐Ruiz, ; Jung et al., ). Therefore, sites reclaimed with substrate materials that have complex structure and a higher availability of nutrients and water and contain forest floor materials should support more diverse and productive understorey plant communities compared to substrate material with less structural complexity and lower nutrient and water availability (Alday et al., ; Kardol & Wardle, ; Zhang & Dong, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil moisture, nutrients and microbial assemblages are critical determinants of seed germination and plant growth and development; whereas, soil texture is important for the development of plant roots (Jung, Duan, House, & Chang, ) and for the retention of water and nutrients in the soil (Hillel, ; Leatherdale, Chanasyk, & Quideau, ). Furthermore, forest floor material typically contains a large seed bank that can be beneficial for establishing a plant community during restoration/reclamation (Alday, Pallavicini, Marrs, & Martínez‐Ruiz, ; Jung et al., ). Therefore, sites reclaimed with substrate materials that have complex structure and a higher availability of nutrients and water and contain forest floor materials should support more diverse and productive understorey plant communities compared to substrate material with less structural complexity and lower nutrient and water availability (Alday et al., ; Kardol & Wardle, ; Zhang & Dong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, forest floor material typically contains a large seed bank that can be beneficial for establishing a plant community during restoration/reclamation (Alday, Pallavicini, Marrs, & Martínez‐Ruiz, ; Jung et al., ). Therefore, sites reclaimed with substrate materials that have complex structure and a higher availability of nutrients and water and contain forest floor materials should support more diverse and productive understorey plant communities compared to substrate material with less structural complexity and lower nutrient and water availability (Alday et al., ; Kardol & Wardle, ; Zhang & Dong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Restoring mined areas to their original ecosystem is not easy because in many cases mining creates a new environment that may not reproduce the same features or function as the pre-mining conditions (Dragovich and Patterson 1995;Court et al 1996;Alday et al 2011b). At Myall Lakes National Park, Australia, Buckney and Morrison (1992) found clear differences in species composition along a temporal gradient between recently disturbed areas and pre-mining sand dune locations.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the main goal of ecosystem restoration is to recover species composition, structure and the function of the original ecosystem prior to disturbance (BRADSHAW, 1990;MACMAHON, 1997;ALDAY et al, 2011a), the results from the "Pilot Restoration Project" (PRP) evidenced two major aspects: i) the inadequacy of taking into account solely the survival of former planted tree species as an indicator of success in restoration programs, once natural regeneration is the most important factor; ii) the preponderant importance of an appropriate species selection in restoration programs. The PRP evaluation, after 22 years from its implementation, showed that M. scabrella was the only native species that was still alive.…”
Section: Discussionmentioning
confidence: 99%